Функціональна семантика прикметників «матеріальна цінність» у дискурсі Джеффрі Чосера - Нікіточкіна, Ірина Володимирівна; Nikitochkina, I. V. (Східноєвропейський національний університет імені Лесі Українки, 2013)
Співвідношення мови й цінностей багатогранне. Мова як метасеміотична система, що описує будь-які артефакти та природний світ, включає у свої смислові структури ціннісні моделі, фіксуючи їх у лексемах. У статті змодельовано лексико-семантичне поле прикметників на позначення матеріальної цінності у структурі дискурсу Джеффрі Чосера. Проведено аналіз функціональної семантики зазначених прикметників. Визначено місце категорії «матеріальна цінність» та вирізнено загальні тенденції репрезентації ціннісних феноменів у середньоанглійській мовній картині світу. The interrelations between language and the system of values are multifaceted. The language as metasemiotic system describes all artifacts and natural world, it includes value models into its notional structures by fixing them with the help of lexemes. The present paper is an investigation of adjectives «material value» in Geoffrey Chaucer’s discourse where their LSF has been modeled. The LSF has been structured into four lexico-semantic groups, its core and peripheral zones have also been defined. The research of the functional semantics of the adjectives under consideration has been presented. The status of the category «material value» in the Middle English language world view has been determined and general representation tendencies of the value phenomena have been highlighted. The results of the given research prove that the Middle English adjectives under consideration were commonly used to describe the objects possessing some/no material value or sometimes to characterize individuals owing some/no material values.
The Functional Semantics of Adjectives «Material Value» in Geoffrey Chaucer’s Discourse
Keywords: дискурс; discourse; категорія «матеріальна цінність»; category of «material value»; прикметник; adjectives